A Deterministic Inventory Model of Deteriorating Items with Two Rates of Production, Shortages, and Variable Production Cycle. (26th July 2011) - Bhowmick, Jhuma; Samanta, G. P.
Abstract : A Continuous production control inventory model is developed for a deteriorating item having shortages and variable production cycle. It is assumed that the production rate is changed to another at a time when the inventory level reaches a prefixed levelQ 1 and continued until the inventory level reaches the levelS ( > Q 1 ) . The demand rate is assumed to be constant, and the production cycle T is taken as variable. The production is started again at a time when the shortage level reaches a prefixed quantityQ 2 . For this model, the total cost per unit time as a function ofQ 1, Q 2, S, and T is derived. The optimal decision rules forQ 1, Q 2, S, and T are computed. The sensitivity of the optimal solution towards changes in the values of different system parameters is also studied. Results are illustrated by numerical examples.